2017
DOI: 10.1002/ptr.5977
|View full text |Cite
|
Sign up to set email alerts
|

What phytotherapy needs: Evidence‐based guidelines for better clinical practice

Abstract: In recent decades, the pharmacological properties of numerous medicinal plants and opportunities in phytotherapy have been explored through research projects, reviews, and monographs. These studies confirm that medicinal plants offer new approaches to tackling diseases. However, improvement of phytotherapy in clinical practice relies on a number of critical factors. In particular, the studies are very heterogeneous, and results and their interpretation by healthcare workers vary greatly, so preventing consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 54 publications
1
61
0
Order By: Relevance
“…Although the facts showed that herbal remedies are generally better tolerated than synthetic medications (Baghernya, Nobili, Blesso, & Sahebkar, ; Colalto, ; Hadi, Pourmasoumi, Najafgholizadeh, Kafeshani, & Sahebkar, ), there is a lack of conclusive information in efficacy and their possible side effects on diseases, which made it one of the most important problems faced by doctors (Hadi, Mohammadi, Hadi, Roshanravan, & Kafeshani, ; Izzo, Hoon‐Kim, Radhakrishnan, & Williamson, ). In this case, a comprehensive systematic review of available clinical trials can represent the most reliable evidence of medicinal plant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the facts showed that herbal remedies are generally better tolerated than synthetic medications (Baghernya, Nobili, Blesso, & Sahebkar, ; Colalto, ; Hadi, Pourmasoumi, Najafgholizadeh, Kafeshani, & Sahebkar, ), there is a lack of conclusive information in efficacy and their possible side effects on diseases, which made it one of the most important problems faced by doctors (Hadi, Mohammadi, Hadi, Roshanravan, & Kafeshani, ; Izzo, Hoon‐Kim, Radhakrishnan, & Williamson, ). In this case, a comprehensive systematic review of available clinical trials can represent the most reliable evidence of medicinal plant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, many advances have been made in research conducted on herbs with weight‐loss properties, many of which have supported the effectiveness of medicinal plants in the treatment of obesity and metabolic syndrome factors. Regarding the fact that systematic review studies produce the highest level of evidence, this study aimed to investigate the efficacy, safety and mechanisms of effective herbal medicines in the management and treatment of obesity and metabolic syndrome in RCTs (Colalto, ; Izzo et al, ). All plants with therapeutic effects on obesity and components of the metabolic syndrome are summarized in Tables 3, 4, and 5 (Supplementary).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review and meta‐analysis, a widely acceptable research method, is at the top in the hierarchy of the evidence assessment (Colalto, ; Izzo, Hoon‐Kim, Radhakrishnan, & Williamson, ). However, to the best of our knowledge, there has been no evaluation of the clinical evidence regarding CSD as intervention for blood lipid in evidence‐based medicine.…”
Section: Discussionmentioning
confidence: 99%